Building traditional classroom techniques in an online course discussion. - David A Line (Academic Chairpersons Conference Proceedings, 2017)
Discussions build connections, increase instructor presence, and develop key points in online courses. Discussions correspond to the classroom in traditional education. They can take the shape of speed dating, lectures, seminars, meetings, and various forms of group work. This session explores ways of getting the most out of online discussions.
Keywords: Online Discussions Connections Points Format